An efficient quasi-solid-state dye-sensitized solar cell with gradient polyaniline-graphene/PtNi tailored gel electrolyte. (1st September 2019) - Liu, Liming; Wu, Yanhua; Chi, Feng; Yi, Zichuan; Wang, Honghang; Li, Wanshu; Zhang, Yan; Zhang, Xiaowen
Abstract: Quasi-solid-state dye-sensitized solar cells from polymer gel electrolytes are promising candidates to stabilize the photovoltaic performances. We demonstrate here the synthesis of a conducting gel electrolyte with gradient polyaniline-graphene/PtNi distribution and redox iodide/triiodide couples in a three-dimensional poly(acrylic acid)-poly(ethylene glycol) matrix. Through sandwiching poly(acrylic acid)-poly(ethylene glycol)/polyaniline-graphene/PtNi gel electrolyte with a dye-sensitized TiO2 photoanode and a PtNi counter electrode, the electrons flow from PtNi counter electrode to conducting gel electrolyte along gradient energy levels for reducing triiodide ions and shortening charge diffusion length. These gradient quasi-solid-state dye-sensitized solar cells achieve a maximized power conversion efficiency of 8.64% in comparison with 7.41% for the device with homogeneously distributed polyaniline-graphene/PtNi, not to mention 5.92% for poly(acrylic acid)-poly(ethylene glycol) tailored solar cell free of polyaniline-graphene/PtNi. Moreover, the optimized quasi-solid-state dye-sensitized solar cell presents a relatively high stability at room temperature over 10 days. Graphical abstract: Image 10111137 Highlights: PANi-G/PtNi is imbibed into PAA-PEG framework assisted by magnetic field. The PANi-G/PtNi has a gradient distribution in gel electrolyte. The PAA-PEG/PANi-G/PtNi electrolyte presents gradient work function. The gel electrolyte presents catalytic activity toward triiodide reduction reaction. The quasi-solid-state DSC shows maximized efficiency of 8.64%.